Frequency Of Depressive And Anxiety Symptoms Among Patients On Interferon And Pegylated Interferon - Muhammad Waseem Shaikh; Farah Ahmad; Gulnaz Shaikh; Syed Hasan Danish; Kirpal Das Makheja; Minhaj A Qidwai (ziauddin University, 2024)
Background: Chronic Hepatitis C (CHC) is highly prevalent in Pakistan. Current standard treatment is Interferon alpha/ Peginterferon with oral ribavirin. Interferon therapy is associated with development & worsening of depressive symptoms in CHC patients and to determine the frequency of depressive and anxiety symptoms among patients on treatment with interferon/ Pegasus. Methods: This cross sectional study was conducted at OPD of Liaquat University Hospital Hyderabad during a period of 4 months (from July2013 to October2013). A sample of 120 patients aged 18-60 years, either currently receiving interferon/ Pegasus treatment or had received that treatment during last 12 months was taken. Known cases of anxiety, depression and those suffering from other debilitating co morbid conditions like carcinoma & non-consenting were excluded. Ethical approval was taken from LUH ethical review committee. A Proforma was used to gather the data. The data collected were analyzed using SPSS version 20.0. Mean (±SD) were computed for quantitative variables. Categorical variables (such as gender and outcome variables i.e. anxiety and depressive symptoms) were measured in frequencies and percentages. Stratification was done with regard to age group & gender to see the impact of these on the outcome followed by application of chi-square test with P-value <0.05 taken significant. Results: Total 120 patients were included in the study & 119 completed the questionnaire. Male patients were 55.5%. Mean age of patients was 32.59 ± 8.56 years (Range: 16-56 years). Primary outcome i-e; frequency of depression & anxiety in patients on interferon were 77.3% & 70.6% respectively. (n=92) had depression. Frequency of depression of almost similar in both genders (77.3% in males & 77.4% in females; p value= 0.584), while anxiety was more in females than males (75% vs 68.2%; p value= 0.273). Both psychiatric symptoms increased with increasing age from 16-26 years to 47-56 years of age (p values = 0.432 & 0.736 respectively). Vast majority (86.6%) were treated with interferon while only 13.4% received the PEGylated interferon therapy. Patients treated with PEGylated interferon had less frequency of depression than those treated with interferon (62.5% vs 79.6%; p value= 0.131). Conclusion: Depression and anxiety were found to be common in CHC patients who had been or are being treated with antiviral treatment leading to increased risk of morbidity and mortality. Screening for risk of depression, proper education and timely treatment through anti-depressant followed by close monitoring is mandatory to achieve success in antiviral treatment. Key Words: Hepatitis C, Depressive symptoms, Anxiety, Interferon alpha.